Cohort profile: The National Colorectal Cancer Cohort (NCRCC) study in China - Kun Chen; Meilin Wang; Qian Xiao; Xifeng Wu; Shu Zheng; Zhizhong Pan; Jiaqi Chen; Zhaoxu Zheng; Yingshuang Zhu; Yeting Hu; Xiangxing Kong; Ye Wei; et al. (BMJ Open)
Purpose The National Colorectal Cancer Cohort (NCRCC) study aims to specifically assess risk factors and biomarkers related to endpoints across the colorectal cancer continuum from the aetiology through survivorship.Participants The NCRCC study includes the Colorectal Cancer Screening Cohort (CRCSC), which recruited individuals who were at high risk of CRC between 2016 and 2020 and Colorectal Cancer Patients Cohort (CRCPC), which recruited newly diagnosed patients with CRC between 2015 and 2020. Data collection was based on questionnaires and abstraction from electronic medical record. Items included demographic and lifestyle factors, clinical information, survivorship endpoints and other information. Multiple biospecimens including blood, tissue and urine samples were collected. Participants in CRCSC were followed by a combination of periodic survey every 5 years and annual linkage with regional or national cancer and death registries for at least 10 years. In CRCPC, follow-up was conducted with both active and passive approaches at 6, 12, 18, 24, 36, 48 and 60 months after surgery.Findings to date A total of 19 377 participants and 15 551 patients with CRC were recruited in CRCSC and in CRCPC, respectively. In CRCSC, 48.0% were men, and the average age of participants at enrolment was 58.7±8.3 years. In CRCPC, 61.4% were men, and the average age was 60.3±12.3 years with 18.9% of participants under 50 years of age.Future plans Longitudinal data and biospecimens will continue to be collected. Based on the cohorts, several studies to assess risk factors and biomarkers for CRC or its survivorship will be conducted, ultimately providing research evidence from Chinese population and optimising evidence-based guidelines across the CRC continuum.